Carbon burial over the last four millennia is regulated by both climatic and land use change. (26th February 2020) - Mao, Jinhua; Burdett, Heidi L.; McGill, Rona A. R.; Newton, Jason; Gulliver, Pauline; Kamenos, Nicholas A.
Abstract: Carbon sequestration by sediments and vegetated marine systems contributes to atmospheric carbon drawdown, but little empirical evidence is available to help separate the effects of climate change and other anthropogenic activities on carbon burial over centennial timescales. We used marine sediment organic carbon to determine the role of historic climate variability and human habitation in carbon burial over the past 5, 071 years. There was centennial‐scale sensitivity of carbon supply and burial to climatic variability, with Little Ice Age cooling causing an abrupt ecosystem shift and an increase in marine carbon contributions compared to terrestrial carbon. Although land use changes during the late 1800s did not cause marked alteration in average carbon burial, they did lead to marked increases in the spatial variability of carbon burial. Thus, while carbon burial by vegetated systems is expected to increase with projected climate warming over the coming century, ecosystem restructuring caused by abrupt climate change may produce unexpected change in carbon burial whose variability is also modulated by land use change. Abstract : Carbon sequestration by sediments and vegetated marine systems contributes to atmospheric carbon drawdown mitigating climate change. Little is known about how climate change and land use interaction will impact carbon sequestration. Using historic carbon burial by a marine vegetated system, we show that in the future while carbon burial is expected to increase with projected climate warming, ecosystem restructuring caused by abrupt climate change may produce unexpected change in carbon burial also modulated by land use change.